(untitled) (mathematica didactica, 2025)
This paper presents a comprehensive exploration of data-based modeling as a strategic approach to develop statistical literacy among upper secondary students. We detail a process framework that was implemented as part of a student laboratory, following specific content and methodical design principles. We assess the model’s application, acknowledging its educational contributions, pinpointing areas requiring refinement, and identifying gaps in current understanding. The implementation demonstrated benefits, especially in fostering students’ engagement and comprehension of statistical concepts.